The Effect of Salicylic Acid on Some Physiological Reactions of Fenugreek (Trigonella foenum-graecum) Under Salinity Stress - A. Pasandi Pour; H. Farahbakhsh; M. Saffari; B. Karamat (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2013)
This study performed to investigate the effects different concentrations of salicylic acid (0, 5, 10, 15 and 20 µM) on membrane lipid peroxidation of fenugreek under levels of salinity stress (0, 50, 100, 150 and 200 mM) in hydroponic condition. The experiment conducted as factorial, in completely randomized design with three replications. Results showed that in plants treated with salinity, chlorophyll a, chlorophyll b and carotenoid contents were reduced in comparison with control plants. However, the salinity increased MDA, other aldehydes, catalase and peroxidase activity in shoots. Results also indicted that applying salicylic acid, especially with concentration of 10 and 15µM, increased the membrane lipid peroxidation and decreased the membrane stability index as compared to the control plants. Results also showed that using 5µM salicylic acid did not significantly improve the salt stress effects compared to the control plants. However, concentration of 20µM salicylic acid increased stress, and decreased the above mentioned parameters.